Empowerment of Women: A Feminist Aspect of Shahraz’s “The Discovery” - Sabahat Rafique (University of Chitral Journal of Linguistics and Literature, 2023)
Garner (1999) and Moghadam (1992) explicate that feminism keeps providing strategies for the empowerment of women. Their struggle against the male-dominating culture and effort to break traditional and patriarchal social shackles is a step towards the equality as well as empowerment of women. Zalewski and Runyan (2013) elucidate that feminism have boundary smashing activities along with philosophies for the empowerment of women with the help of re-ordering institutions globally for gender roles.   Tyson (2006) relates this phenomenon to traditional roles regarding gender as a social construction for keeping women powerless and elevating men’s point of view. Savitt (1982) explains that all stereotype characters in literature highlight the narrowness as well as confining nature of female characters in literature, where they are mostly portrayed as incompetent, meek,  dependent, helpless, troubled, and fearful creatures, while at the same time, males are presented as authoritative and powerful. Women are allotted and given subservient and passive roles to facilitate men's depriving them of their rights easily. Shahraz’s selected story breaks such tradition and presents her female protagonist as a confident, independent, educated, and empowered woman who refuses to compromise on her self-respect and decides to live alone with her future baby.